2011
DOI: 10.1002/cjce.20545
|View full text |Cite
|
Sign up to set email alerts
|

Ni catalysts supported on activated carbon from petcoke and their activity for toluene hydrogenation

Abstract: Petroleum coke (petcoke) is an abundant resource that can potentially be converted to catalyst support materials through activation to increase the surface area and reduce the sulphur content. In this work, potassium hydroxide (KOH) catalysed activation was employed with petcoke to produce activated carbons, which were characterised with nitrogen physisorption, X‐ray diffraction, scanning electron microscopy and temperature‐programmed reduction. With activation temperatures between 500 and 800°C, the surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This catalyst will be referred to as Ni/AC. A previous study has shown that a Ni catalyst prepared by this method had comparable performance to a Ni catalyst supported on a commercial activated carbon (Darco ® G-60) for the hydrogenation of toluene [18]. Deactivated catalysts were prepared by impregnating with vanadium to simulate hydrodemetallization (HDM) and by exposure to ethylene to induce coking.…”
Section: Catalyst Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…This catalyst will be referred to as Ni/AC. A previous study has shown that a Ni catalyst prepared by this method had comparable performance to a Ni catalyst supported on a commercial activated carbon (Darco ® G-60) for the hydrogenation of toluene [18]. Deactivated catalysts were prepared by impregnating with vanadium to simulate hydrodemetallization (HDM) and by exposure to ethylene to induce coking.…”
Section: Catalyst Synthesismentioning
confidence: 99%
“…The activated carbon was prepared by chemical activation as described previously [18]. Briefly, raw delayed petroleum coke (petcoke, Suncor Energy Inc., Calgary, AB, Canada) was ball milled and sieved to 44-149 m and then mixed with potassium hydroxide (KOH, 85%, Alfa Aesar) in a dry mass ratio of 3:1 (KOH: petcoke).…”
Section: Activation Of Petroleum Cokementioning
confidence: 99%
“…In the first set of catalysts, the activated petcoke is a support for the active metal (in this case, Ni) . Chemical activation with potassium hydroxide at various temperatures was used to prepare the activated carbon from delayed coke.…”
Section: Activated Petcoke As a Catalyst Or Catalyst Supportmentioning
confidence: 99%
“…In the first set of catalysts, the activated petcoke is a support for the active metal (in this case, Ni). [24] Chemical activation with potassium hydroxide at various temperatures was used to prepare the activated carbon from delayed coke. Wet impregnation was used to add Ni to the supports and the catalysts were tested in a plug flow reactor at 1.38 MPa, 563 K, and a liquid hourly space velocity of 2.4/h using toluene hydrogenation as a model reaction.…”
Section: Supportmentioning
confidence: 99%
See 1 more Smart Citation